1998
DOI: 10.1016/s1074-7613(00)80635-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of CD8 Coreceptor Function Revealed by Crystallographic Analysis of a Murine CD8αα Ectodomain Fragment in Complex with H-2Kb

Abstract: The crystal structure of the two immunoglobulin variable-like domains of the murine CD8alphaalpha homodimer complexed to the class I MHC H-2Kb molecule at 2.8 A resolution shows that CD8alphaalpha binds to the protruding MHC alpha3 domain loop in an antibody-like manner. Comparison of mouse CD8alphaalpha/H-2Kb and human CD8alphaalpha/HLA-A2 complexes reveals shared as well as species-specific recognition features. In both species, coreceptor function apparently involves the participation of CD8 dimer in a bide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
196
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(207 citation statements)
references
References 57 publications
11
196
0
Order By: Relevance
“…Both the CD8 ␣-and ␤-chains are composed of a single extracellular Ig superfamily (IgSF) 3 variable (V) domain, a membrane-proximal hinge (H) region, a transmembrane domain (TM), and a cytoplasmic tail (CY). Biochemical and structural studies have shown that the Ig V domain of CD8␣, in conjunction with that of CD8␤, interacts with MHC class I molecules, thereby allowing the CD8 molecule to function as a coreceptor of the T cell Ag receptor (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Both the CD8 ␣-and ␤-chains are composed of a single extracellular Ig superfamily (IgSF) 3 variable (V) domain, a membrane-proximal hinge (H) region, a transmembrane domain (TM), and a cytoplasmic tail (CY). Biochemical and structural studies have shown that the Ig V domain of CD8␣, in conjunction with that of CD8␤, interacts with MHC class I molecules, thereby allowing the CD8 molecule to function as a coreceptor of the T cell Ag receptor (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The molecular interactions between CD8aa and MHCI molecules have been revealed by X-ray crystallographic studies in complexes of mouse CD8aa and its ligands, K b and TL, and also in complexes of human CD8aa and its ligand, HLA-A2 [21][22][23]. In both mouse and human CD8aa/pMHCI complexes, two CD8a subunits bind asymmetrically to pMHCI [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In both mouse and human CD8aa/pMHCI complexes, two CD8a subunits bind asymmetrically to pMHCI [21,22]. One subunit is involved in the dominant interaction that contributes to more than 70% of the total interaction surface between CD8 and pMHCI, the other subunit interacts only with the MHCI a3 domain [21,22]. The molecular structures of mouse CD8aa-complexed with K b and mouse CD8ab are very similar [24], suggesting that the CD8a or CD8b subunit in the CD8ab/pMHCI complex may mediate a dominant interaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations